Jumma Nation and Persecution in Bangladesh - Chakma, Jhubhur (Journal of International Buddhist Studies, 2021)
This paper deals with the religious and political persecutions that have become a serious concern to the religious and ethnic minority groups known as ‘Jumma’ people of CHT in Bangladesh namely, the Chakma, Marma, Thangchangya, Tripura, Rakhine, Chak, Bawm, Phangkhua, Khumi, Khyang, and Mro. The Jumma people practice Buddhism, Hinduism, Christianity, and a few others are animists while the majority mainstream population follow Islam, and Islam has been constitutionally adopted as the state religion. Wide-scale exclusion in association with religio-political persecution became forceful soon after the constitutional adoption of Islam as the state religion a few years after independence. Hence, from the perspective of religious studies, this study tends to focus on the plight of religious persecution linked to violence being meted out to the Jumma people. As per the information available, violence in CHT is multi-faceted and multiple in nature. Usually, the ongoing violence and conflicts occur as one-sided communal attacks inevitably leading to rioting, arson, plundering, killing, rape, land occupation, and finally interference by the army and law & order forces that resulted in arbitrary arrest, torture, fabricated cases, and putting in unbailable imprisonment.